PENGARUH PROFESIONALISME AUDITOR, INDEPENDENSI AUDITOR, DAN KOMPETENSI AUDITOR TERHADAP KUALITAS AUDIT - Kristianto, Oktavianus; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of the researchis to examine the influence of auditor professionalism, auditor independence, and auditor competence to the audit quality. Auditor professionalism is reflected by the indicatorsi.e.: dedication to the profession, social obligation, independence, belief in profession and relationship with others whereas auditor independence is reflected by the old indicator i.e.client relationship, client pressure, auditor partner analysis, and non-audit services then auditorcompetence is reflected by indicators i.e.knowledge and experience.Theprimary datais used in this research and it has been carried out by using survey method and purposive sampling technique to the 65 respondents from 15 PAFs which are located in Surabaya and listed in Indonesian Institute of Certified Public Accountants in 2016.The result of multiple linear regressions shows that professionalism and auditor competence give positive influenceto the audit quality whereas auditor independence does not give anyinfluenceto the R2is 56.3% whereas the remaining is 43.7% is influenced by other factor.Keywords : auditor professionalism, auditor independence, auditor competence, audit quality